Porous active material surface bionic modification layer and preparation method thereof
By inducing the preparation of a hydroxyapatite coating on the surface of the active metal porous material, the problems of insufficient bonding strength between the porous active material coating and the material and low antibacterial effect are solved, and the controllable degradation and biological activity of the porous alloy material are achieved.
Patent Information
- Application Number
- CN202510026888.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2045-01-08
AI Technical Summary
The coating and material bond strength of the existing porous active materials is limited, has low strength, and has low antibacterial effect, so the biological activity still needs to be further improved.
The hydroxyapatite coating was prepared by inducing the surface of the active metal porous material, and the lysozyme mineralized bionic solution was used for treatment to form a bionic modified layer on the surface of the porous active material, which had excellent antibacterial properties, osteopromoting integration and good mechanical strength.
Controllable degradation of porous alloy materials is achieved, suitable for bone implants, improves the bonding strength between the coating and the material, and enhances the antibacterial effect and biological activity.
Smart Images

Figure CN119405893A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alloy coating preparation technology, in particular to a porous active material surface bionic modified layer and a preparation method thereof. Background Art
[0002] Degradable active metal materials, such as titanium alloys, magnesium alloys, zinc alloys, iron-based alloys, etc., have been widely favored by researchers in recent years due to their advantages such as good toughness, degradation products that are beneficial to the human body, and no need for secondary surgery to remove them. Although their elastic modulus (40-50GPa) is closer to that of human compact bone (1-30GPa), they still need to be made into porous structures to effectively reduce their elastic modulus to prevent the occurrence of problems such as stress shielding. Selective Laser Melting (SLM), as an effective means of preparing complex gradient porous structures, has been widely used in the orthopedic field of commonly used medical devices such as large bone defects, stents, and intervertebral fusion devices. However, biodegradable materials represented by titanium alloys and magnesium alloys have poor corrosion resistance and will degrade faster in physiological environments. The porous structure design increases the specific surface area of the implant, further increasing its corrosion rate, leading to premature failure of bone implants, local hydrogen accumulation, and an overly alkaline microenvironment. These problems limit the further application of biodegradable active metals in biomedical fields such as tissue engineering scaffolds, cardiovascular stents, and bone implant devices.
[0003] For active metal materials that are not resistant to corrosion, surface modification methods such as micro-arc oxidation are often used to protect them as a whole. However, since the structure of porous materials is more complex than that of solid materials, it is difficult to modify their surfaces using conventional methods. Although Chinese patents CN 118563386A "Preparation method and application of intelligent self-repairing coating based on new sealing treatment micro-arc oxidation coating" and CN 116618273A "Method for preparing composite biological coating on magnesium alloy micro-arc oxidation coating" both mention post-treatment of micro-arc oxidation coating to prepare composite coating, and micro-arc oxidation (MAO) technology, as a method of in-situ generation of ceramic film layer on alloy surface by high temperature and high pressure generated by arc discharge, has been widely used in the field of surface modification in recent years, there are a large number of micron-level holes and defects on the outside of the coating prepared by micro-arc oxidation, which increases the erosion opportunities of corrosive ions and microorganisms and weakens the corrosion resistance of MAO film. Therefore, this technology still needs to be combined with other means to prepare composite coating to enhance its corrosion resistance. Other methods such as spraying, surface coating, chemical conversion, etc. still have problems such as complex processing technology, insufficient wettability and limited bonding strength. In addition, the coatings prepared at this stage do not have the growth environment required for bone tissue simulation. They are only for the purpose of preparing wear-resistant and corrosion-resistant coatings on the substrate surface, without considering the sequential growth effect of three-dimensional bone tissue.
[0004] Chinese patent CN115120783A "A porous titanium-based antibacterial active material and its preparation method and application" discloses a porous titanium-based antibacterial active material including a porous titanium-based alloy material and a bioactive coating. The tantalum coating and the silver-containing hydroxyapatite layer are prepared by physical vapor deposition technology. The hydroxyapatite layer prepared by cold spraying has high crystallinity and is not easy to degrade. However, the bonding strength between the porous titanium-based antibacterial active material coating and the material is limited, the strength is not high, and its antibacterial effect is low, and its biological activity still needs to be further improved.
[0005] Therefore, it is of great significance to develop a bionic modified layer on the surface of a porous active material with high bonding strength and the ability to effectively improve the electrochemical performance of lithium-ion batteries, as well as a preparation method and application thereof. Summary of the invention
[0006] In view of the fact that the existing porous active materials have limited bonding strength between the coating and the material, low strength, low antibacterial effect, and the problem that the biological activity still needs to be further improved, the present invention provides a bionic modified layer on the surface of a porous active material and a preparation method thereof. A hydroxyapatite coating is induced on the surface of an active metal porous material to obtain a bionic modified layer on the surface of the porous active material. The bionic modified layer has excellent antibacterial properties, bone integration promoting properties, and good mechanical strength, can achieve controllable degradation of porous alloy materials, and is suitable for bone implants.
[0007] To achieve the above object, the technical solution adopted by the present invention is: A method for preparing a bionic modified layer on the surface of a porous active material comprises the following steps: S1. An active metal porous material having a pore size of 400-2000 μm and a porosity of 40-80% is prepared by SLM, and pre-treated, the pre-treatment comprising surface sandblasting, ultrasonic cleaning, repeating the ultrasonic cleaning step 3-5 times, drying, and standby; S2. The lysozyme is mixed with a cell buffer to obtain a lysozyme solution; the cell buffer is mixed with a reducing agent in the same proportion and the same composition, and the pH is adjusted to 5-6.8 to obtain a reducing agent solution; the lysozyme solution and the reducing agent solution are mixed in equal volumes to obtain a lysozyme mineralized biomimetic solution for use; S3. Immerse the active metal porous material obtained in S1 into the lysozyme mineralized biomimetic solution obtained in S2, incubate, take out and put into a circulation pump containing the lysozyme mineralized biomimetic solution obtained in S2, circulate at 0.5-2mL / min for 15-20min, repeat 3-5 times, wash and dry, and obtain the biomimetic modified layer on the surface of the porous active material.
[0008] Furthermore, the active metal porous material described in S1 is one or more of titanium-based materials, magnesium-based materials, iron-based materials, and zinc-based materials; the porous structure in the active metal porous material described in S1 is one or more of body-centered cubic, face-centered cubic, regular octahedron, and triple minimal surface.
[0009] Furthermore, the cleaning medium in the ultrasonic cleaning in S1 is one or more of 5-20 vol.% perchloric acid alcohol, 3-5 vol.% nitric acid alcohol, and 10-20 vol.% dilute hydrochloric acid, the vibration frequency is 10-20 kHz, and the ultrasonic time is 10-20 min.
[0010] The preferred vibration frequency of the ultrasonic treatment in the present invention is 10-20kHz, the ultrasonic time is 10-20min, and the above steps are repeated at least 3 times to completely rinse away the sticky powder and corrosion peeling products in the porous material, ensuring that the active metal material is covered with a relatively dense oxide film as a whole, and will not peel off on a large scale due to subsequent treatment, which is beneficial to improving the formation effect of the bionic modified layer on the surface of the porous active material.
[0011] Furthermore, the drying in S1 is to dry the entire structure by using an inert gas sprayed with high pressure, and the inert gas is 99.999 vol.% high-purity argon and / or nitrogen.
[0012] The present invention preferably uses 99.999 vol.% high-purity argon and / or nitrogen to dry the active metal porous material as a whole, so as to avoid bringing the corrosive liquid into the interior of the active metal porous material, causing possible large-area oxidation, thereby affecting the formation effect of the bionic modified layer on the surface of the porous active material.
[0013] Furthermore, the cell buffer in S2 contains one or more of 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid, N-(2-acetamido)-2-aminoethanesulfonic acid, and 3-(N-morpholino)propanesulfonic acid; and the pH of the cell buffer is 7-8.
[0014] The present invention preferably controls the pH value of the cell buffer to between 7 and 8, that is, the entire liquid environment needs to be stabilized in a neutral or weakly alkaline environment to facilitate the subsequent bionic mineralization effect on the surface of the active metal porous material, making it easier to grow a hydroxyapatite protective layer on its surface.
[0015] Furthermore, the reducing agent in S2 is one or more of tris(2-carboxyethyl)phosphine hydrochloride, dithiothreitol, and tris(3-hydroxypropyl)phosphine.
[0016] The preferred reducing agent of the present invention is a reducing agent for disulfide bonds in protein chemistry and proteomics research, so as to prevent the intramolecular or intermolecular disulfide bonds formed between cysteines in proteins, thereby promoting the biomimetic mineralization effect on the surface of the active metal porous material to grow a hydroxyapatite protective layer.
[0017] Furthermore, the pH value in S2 is adjusted to 5-6.8 by using a strong alkaline solvent; the strong alkaline solvent is one or more of NaOH, KOH and Ca(OH)2.
[0018] The preferred strong alkaline solvent of the present invention is NaOH, KOH and Ca(OH)2, which are elements commonly contained in organisms, so as to avoid the introduction of excess ions that are not conducive to the growth of organisms during the treatment process, thereby affecting the formation effect of the bionic modified layer on the surface of the porous active material.
[0019] Furthermore, the incubation in S3 is carried out in a constant temperature box at a temperature of 18-37° C., a relative humidity of 45-60%, and an incubation time of 1.5-3 h.
[0020] The preferred constant temperature box temperature of the present invention is 18-37°C, the relative humidity is 45-60%, and the incubation time is 1.5-3h, so as to prevent the lysozyme mineralization bionic solution from being insufficiently bionic mineralized due to too short storage time; at the same time, it also prevents the lysozyme mineralization bionic solution from absorbing moisture due to too long storage time, and then causing problems such as reduced concentration or even failure, which affects the formation effect of the bionic modified layer on the surface of the porous active material.
[0021] Furthermore, the cleaning in S3 is to use a high-purity organic solvent to fully clean the inside and surface of the porous material; the high-purity organic solvent is one or more of anhydrous ethanol, dimethyl carbonate, and diethyl carbonate; the drying in S3 is to use an inert gas to blow off the residual solution and salt on the surface of the active metal porous material; the inert gas is 99.999 vol.% high-purity argon and / or nitrogen.
[0022] The present invention preferably uses one or more of anhydrous ethanol, dimethyl carbonate and diethyl carbonate as the high-purity organic solvent to avoid residual harmful substances in the porous structure and produce toxic side effects on the implanted organism.
[0023] Another object of the present invention is to provide a bionic modified layer on the surface of a porous active material.
[0024] A porous active material surface bionic modification layer is prepared by any of the above-mentioned methods for preparing a porous active material surface bionic modification layer.
[0025] Compared with the prior art, the present invention has the following advantages and beneficial effects: (1) The method for preparing the bionic modified layer on the surface of porous active materials developed in the present invention is simple and rapid, and is applicable to a variety of active and degradable metal materials. The formed hydroxyapatite in-situ coating is not only tightly bonded to the substrate, but also a uniform bionic modified layer can be obtained on the inner and outer surfaces of different types of active metal porous materials.
[0026] (2) The bionic modified layer on the surface of the porous active material developed in the present invention forms a protective film with a continuous film layer and uniform thickness (about 10 μm) during the preparation process, which not only improves its strength and hardness, but also improves its corrosion resistance, thereby greatly reducing its degradation rate during actual service.
[0027] (3) The bionic modified layer on the surface of the porous active material of the present invention is a hydroxyapatite bionic coating formed in situ on the porous active material. It is prepared by mixing a lysozyme-type solution and a reducing agent solution into a lysozyme mineralized bionic solution. The specific reducing agent of the present invention acts as a chelating agent for various metal ions such as Ti, Zn, Mg, etc., and can stably exist in both alkaline and acidic solutions. It can form a complex with a ring structure on the surface of the porous active material, which plays a role in stabilizing the connection between the surface of the metal matrix and the hydroxyapatite layer grown in situ, thereby obtaining a stable bionic mineralized hydroxyapatite nanofilm layer formed in situ on the porous active material, which cleverly imitates the mineralized bone around the native bone tissue and is very suitable for osteoblasts to adhere to its surface. The porous active metal scaffold formed by the SLM technology forms a plurality of micro-nanopores after surface modification, which promotes further climbing of osteoblasts and further improves their bone integration. Combined with the Mg formed after the degradation of the active metal,2+ 、Zn 2+ , Cu 1+ / Cu 2+ Plasma products show excellent antibacterial properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The invention is further described using the accompanying drawings, but the embodiments in the accompanying drawings do not constitute any limitation to the invention. A person skilled in the art can obtain other drawings based on the following drawings without creative work.
[0029] Figure 1 This is a flow chart for preparing the bionic modified layer on the surface of the porous active material in this application.
[0030] Figure 2 This is the microscopic cross-sectional morphology and element distribution diagram of the bionic modified layer on the surface of the porous active material of this application.
[0031] Figure 3 This is a microscopic morphology diagram of comparative example 1 of the present application.
[0032] Figure 4 This is a physical picture of comparative example 2 of this application.
[0033] Figure 5 This is a physical picture of comparative example 3 of this application.
[0034] Figure 6 This is the internal OM morphology image of comparative example 4 of the present application.
[0035] Figure 7 This is a physical picture of comparative example 5 of this application.
[0036] Figure 8 These are the cell staining images of Example 1 and Comparative Example 6 of the present application, with Comparative Example 6 on the left and Example 1 on the right.
[0037] Fig. 9 This is a cell diagram of the porous active material according to Example 1 of the present application and without any treatment. DETAILED DESCRIPTION
[0038] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention is further described by the following examples. Obviously, the following examples are only part of the embodiments of the present invention, rather than all the embodiments; it should be understood that the embodiments of the present invention are only used to illustrate the technical effects of the present invention, rather than to limit the scope of protection of the present invention.
[0039] The present invention will be specifically described below by examples, and these examples are not intended to limit the present invention in any way. It will be appreciated by those skilled in the art that these examples are only intended to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods for the unrecorded specific conditions in the following examples are usually performed under normal conditions or according to the conditions recommended by the manufacturer. Unless otherwise indicated, percentages and parts are calculated by weight. The following examples are mainly for a better understanding of the analytical method of the present invention and do not exhaust all operating modes. Parts by weight hereinafter may represent conventional unit measurements in the art, such as kilograms, grams, etc., or may represent ratios between the components, such as mass or weight ratios, etc.
[0040] The raw materials in the examples can all be obtained commercially; unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0041] Embodiment 1: A method for preparing a biomimetic modified layer on the surface of a porous active material, comprising the following steps: S1. Prepare a body-centered cubic AZ91D magnesium alloy with a pore size of 550 μm and a porosity of 60% by SLM, and perform pretreatment on it, specifically including using a sandblasting machine to first sandblast the outer layer of sticky powder, and then use a 10 vol.% perchloric acid ethanol solution to ultrasonically treat it for 15 minutes, then take it out and immerse it in an ethanol solution and re-ultrasonic vibrate it for 15 minutes, the vibration frequency is set to 15 kHz, after repeating it 3 times, use a high-purity argon gas with a purity of 99.999 vol.% to blow it dry as a whole, and set it aside; S2. Mix 2 mg / mL lysozyme with 10 mmol / L 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid (HEPES) cell buffer at pH 7-8 to obtain a lysozyme type solution; use the same composition and proportion of the cell buffer to mix with 50 mL of tris(2-carboxyethyl)phosphine hydrochloride (TCEP) reducing agent, adjust the pH to 5.8 with 5 mol / L NaOH strong alkaline solvent to obtain a reducing agent solution; take the lysozyme type solution and the reducing agent solution, mix them in equal volumes, and mix them evenly by ultrasonic vibration to obtain a lysozyme mineralized biomimetic solution for standby use; S3. Use high-purity anhydrous ethanol to fully clean the inside and surface of the active metal porous material, immerse the active metal porous material obtained in S1 into the lysozyme mineralized biomimetic solution obtained in S2, and incubate in a constant temperature box at a temperature of 20°C and a humidity of 55%. Incubate for 2 hours, take it out and put it into a circulation pump containing the lysozyme mineralized biomimetic solution obtained in S2, and circulate it for 18 minutes at 0.8mL / min. Repeat 3 times, immerse the active metal porous material in anhydrous ethanol solvent, set the vibration frequency to 15kHz for ultrasonic vibration, and after completely cleaning the residual solution inside and on the surface of the porous material, use high-purity argon (99.999vol.%) to blow dry the residual solution and salt on the surface of the active metal porous material to obtain the biomimetic modified layer on the surface of the porous active material.
[0042] Embodiment 2: A method for preparing a biomimetic modified layer on the surface of a porous active material, comprising the following steps: S1. Prepare a regular octahedral WE43 magnesium alloy with a pore size of 1310 μm and a porosity of 76% by SLM, and perform pretreatment on it, specifically including using a sandblasting machine to first sandblast the outer layer of sticky powder, and then use a 10 vol.% perchloric acid ethanol solution to ultrasonically treat it for 15 minutes, then take it out and immerse it in an ethanol solution and re-ultrasonic vibrate it for 15 minutes, the vibration frequency is set to 15 kHz, after repeating it 3 times, use a high-purity argon gas with a purity of 99.999 vol.% to blow it dry as a whole, and set it aside; S2. Mix 2 mg / mL lysozyme with 10 mmol / L N-(2-acetamido)-2-aminoethanesulfonic acid (ACES) cell buffer at pH 7-8 to obtain a lysozyme type solution; use the same composition and proportion of the cell buffer to mix with 50 mL of dithiothreitol (DTT) reducing agent, and adjust the pH to 5.8 with 5 mol / L NaOH strong alkaline solvent to obtain a reducing agent solution; take the lysozyme type solution and the reducing agent solution, mix them in equal volumes, and mix them evenly by ultrasonic vibration to obtain a lysozyme mineralized biomimetic solution for standby use; S3. Use high-purity anhydrous ethanol to fully clean the inside and surface of the active metal porous material, immerse the active metal porous material obtained in S1 into the lysozyme mineralized biomimetic solution obtained in S2, and incubate in a constant temperature box at a temperature of 20°C and a humidity of 55%. Incubate for 2 hours, take it out and put it into a circulation pump containing the lysozyme mineralized biomimetic solution obtained in S2, and circulate it at 1.5 mL / min for 20 minutes. Repeat 4 times, immerse the active metal porous material in anhydrous ethanol solvent, set the vibration frequency to 15 kHz for ultrasonic vibration, and after completely cleaning the residual solution inside and on the surface of the porous material, use high-purity argon (99.999 vol.%) to blow dry the residual solution and salt on the surface of the active metal porous material to obtain the biomimetic modified layer on the surface of the porous active material.
[0043] Embodiment 3: A method for preparing a biomimetic modified layer on the surface of a porous active material, comprising the following steps: S1. Prepare body-centered cubic pure Zn with a pore size of 550 μm and a porosity of 60% by SLM, and perform pretreatment on it, specifically including sandblasting the outer layer of sticky powder with a sandblasting machine, and then ultrasonically treating it with a 10 vol.% perchloric acid ethanol solution for 15 minutes, then taking it out and immersing it in an ethanol solution and re-ultrasonic vibrating it for 15 minutes, the vibration frequency is set to 15 kHz, and after repeating it 3 times, use a high-purity argon gas with a purity of 99.999 vol.% to blow it dry as a whole and set it aside; S2. Mix 2 mg / mL lysozyme with 10 mmol / L 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid (HEPES) cell buffer at pH 7-8 to obtain a lysozyme type solution; use the same composition and proportion of the cell buffer to mix with 50 mL of tris(2-carboxyethyl)phosphine hydrochloride (TCEP) reducing agent, adjust the pH to 5.8 with 5 mol / L NaOH strong alkaline solvent to obtain a reducing agent solution; take the lysozyme type solution and the reducing agent solution, mix them in equal volumes, and mix them evenly by ultrasonic vibration to obtain a lysozyme mineralized biomimetic solution for standby use; S3. Use high-purity anhydrous ethanol to fully clean the inside and surface of the active metal porous material, immerse the active metal porous material obtained in S1 into the lysozyme mineralized biomimetic solution obtained in S2, and incubate in a constant temperature box at a temperature of 20°C and a humidity of 55%. Incubate for 2 hours, take it out and put it into a circulation pump containing the lysozyme mineralized biomimetic solution obtained in S2, and circulate it for 18 minutes at 0.8mL / min. Repeat 3 times, immerse the active metal porous material in anhydrous ethanol solvent, set the vibration frequency to 15kHz for ultrasonic vibration, and after completely cleaning the residual solution inside and on the surface of the porous material, use high-purity argon (99.999vol.%) to blow dry the residual solution and salt on the surface of the active metal porous material to obtain the biomimetic modified layer on the surface of the porous active material.
[0044] Embodiment 4: A method for preparing a biomimetic modified layer on the surface of a porous active material, comprising the following steps: S1. Prepare a regular octahedral Zn-Mg-Cu zinc alloy with a pore size of 1310 μm and a porosity of 76% by SLM, and perform pretreatment on it, specifically including using a sandblasting machine to first sandblast the outer layer of sticky powder, and then use a 10 vol.% perchloric acid ethanol solution to ultrasonically treat it for 15 minutes, then take it out and immerse it in an ethanol solution and re-ultrasonic vibrate it for 15 minutes, the vibration frequency is set to 15 kHz, after repeating it 3 times, use a high-purity argon gas with a purity of 99.999 vol.% to blow it dry as a whole, and set it aside; S2. Mix 2 mg / mL lysozyme with 10 mmol / L N-(2-acetamido)-2-aminoethanesulfonic acid (ACES) cell buffer at pH 7-8 to obtain a lysozyme type solution; use the same composition and proportion of the cell buffer to mix with 50 mL of dithiothreitol (DTT) reducing agent, and adjust the pH to 5.8 with 5 mol / L NaOH strong alkaline solvent to obtain a reducing agent solution; take the lysozyme type solution and the reducing agent solution, mix them in equal volumes, and mix them evenly by ultrasonic vibration to obtain a lysozyme mineralized biomimetic solution for standby use; S3. Use high-purity anhydrous ethanol to fully clean the inside and surface of the active metal porous material, immerse the active metal porous material obtained in S1 into the lysozyme mineralized biomimetic solution obtained in S2, and incubate in a constant temperature box at a temperature of 20°C and a humidity of 55%. Incubate for 2 hours, take it out and put it into a circulation pump containing the lysozyme mineralized biomimetic solution obtained in S2, and circulate it at 1.5 mL / min for 20 minutes. Repeat 4 times, immerse the active metal porous material in anhydrous ethanol solvent, set the vibration frequency to 15 kHz for ultrasonic vibration, and after completely cleaning the residual solution inside and on the surface of the porous material, use high-purity argon (99.999 vol.%) to blow dry the residual solution and salt on the surface of the active metal porous material to obtain the biomimetic modified layer on the surface of the porous active material.
[0045] Comparative Example 1: A method for preparing a surface modification layer of a porous active material, comprising the following steps: S1. Prepare a body-centered cubic AZ91D magnesium alloy with a pore size of 550 μm and a porosity of 60% by SLM, and set aside; S2. Mix 2 mg / mL lysozyme with 10 mmol / L 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid (HEPES) cell buffer at pH 7-8 to obtain a lysozyme type solution; use the same composition and proportion of the cell buffer to mix with 50 mL of tris(2-carboxyethyl)phosphine hydrochloride (TCEP) reducing agent, adjust the pH to 5.8 with 5 mol / L NaOH strong alkaline solvent to obtain a reducing agent solution; take the lysozyme type solution and the reducing agent solution, mix them in equal volumes, and mix them evenly by ultrasonic vibration to obtain a lysozyme mineralized biomimetic solution for standby use; S3. Use high-purity anhydrous ethanol to fully clean the inside and surface of the active metal porous material, immerse the active metal porous material obtained in S1 into the lysozyme mineralized biomimetic solution obtained in S2, and incubate in a constant temperature box at a temperature of 20°C and a humidity of 55%. Incubate for 2 hours, take it out and put it into a circulation pump containing the lysozyme mineralized biomimetic solution obtained in S2, and circulate it for 18 minutes at 0.8mL / min. Repeat 3 times, immerse the active metal porous material in anhydrous ethanol solvent, set the vibration frequency to 15kHz for ultrasonic vibration, and after completely cleaning the residual solution inside and on the surface of the porous material, use high-purity argon (99.999vol.%) to blow dry the residual solution and salt on the surface of the active metal porous material to obtain the surface modification layer of the porous active material.
[0046] Compared with Example 1, the main difference of this comparative example is that the active metal porous material is not pre-treated.
[0047] Comparative Example 2: A method for preparing a surface modification layer of a porous active material, comprising the following steps: S1. Prepare a body-centered cubic AZ91D magnesium alloy with a pore size of 3000 μm and a porosity of 86.4% by SLM, and perform pretreatment on it, specifically including using a sandblasting machine to first sandblast the outer layer of sticky powder, and then use a 10 vol.% perchloric acid ethanol solution to ultrasonically treat it for 15 minutes, then take it out and immerse it in an ethanol solution and re-ultrasonic vibrate it for 15 minutes, the vibration frequency is set to 15 kHz, after repeating it 3 times, use a high-purity argon gas with a purity of 99.999 vol.% to blow it dry as a whole, and set it aside; S2. Mix 2 mg / mL lysozyme with 10 mmol / L 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid (HEPES) cell buffer at pH 7-8 to obtain a lysozyme type solution; use the same composition and proportion of the cell buffer to mix with 50 mL of tris(2-carboxyethyl)phosphine hydrochloride (TCEP) reducing agent, adjust the pH to 5.8 with 5 mol / L NaOH strong alkaline solvent to obtain a reducing agent solution; take the lysozyme type solution and the reducing agent solution, mix them in equal volumes, and mix them evenly by ultrasonic vibration to obtain a lysozyme mineralized biomimetic solution for standby use; S3. Use high-purity anhydrous ethanol to fully clean the inside and surface of the active metal porous material, immerse the active metal porous material obtained in S1 into the lysozyme mineralized biomimetic solution obtained in S2, and incubate in a constant temperature box at a temperature of 20°C and a humidity of 55%. Incubate for 2 hours, take it out and put it into a circulation pump containing the lysozyme mineralized biomimetic solution obtained in S2, and circulate it at 1.5 mL / min for 20 minutes. Repeat 4 times, immerse the active metal porous material in anhydrous ethanol solvent, set the vibration frequency to 15 kHz for ultrasonic vibration, and after completely cleaning the residual solution inside and on the surface of the porous material, use high-purity argon (99.999 vol.%) to blow dry the residual solution and salt on the surface of the active metal porous material to obtain the surface modification layer of the porous active material.
[0048] Compared with Example 1, the main difference of this comparative example is that the pore size and porosity of the active metal porous material are too large.
[0049] Comparative Example 3: A method for preparing a surface modification layer of a porous active material, comprising the following steps: S1. Prepare a regular octahedral WE43 magnesium alloy with a pore size of 150 μm and a porosity of 34.5% by SLM, and perform pretreatment on it, specifically including using a sandblasting machine to first sandblast the outer layer of sticky powder, and then use a 10 vol.% perchloric acid ethanol solution to ultrasonically treat it for 15 minutes, then take it out and immerse it in an ethanol solution and re-ultrasonic vibrate it for 15 minutes, the vibration frequency is set to 15 kHz, after repeating it 3 times, use a high-purity argon gas with a purity of 99.999 vol.% to blow it dry as a whole, and set it aside; S2. Mix 2 mg / mL lysozyme with 10 mmol / L N-(2-acetamido)-2-aminoethanesulfonic acid (ACES) cell buffer at pH 7-8 to obtain a lysozyme type solution; use the same composition and proportion of the cell buffer to mix with 50 mL of dithiothreitol (DTT) reducing agent, and adjust the pH to 5.8 with 5 mol / L NaOH strong alkaline solvent to obtain a reducing agent solution; take the lysozyme type solution and the reducing agent solution, mix them in equal volumes, and mix them evenly by ultrasonic vibration to obtain a lysozyme mineralized biomimetic solution for standby use; S3. Use high-purity anhydrous ethanol to fully clean the inside and surface of the active metal porous material, immerse the active metal porous material obtained in S1 into the lysozyme mineralized biomimetic solution obtained in S2, and incubate in a constant temperature box at a temperature of 20°C and a humidity of 55%. Incubate for 2 hours, take it out and put it into a circulation pump containing the lysozyme mineralized biomimetic solution obtained in S2, and circulate it for 18 minutes at 0.8mL / min. Repeat 3 times, immerse the active metal porous material in anhydrous ethanol solvent, set the vibration frequency to 15kHz for ultrasonic vibration, and after completely cleaning the residual solution inside and on the surface of the porous material, use high-purity argon (99.999vol.%) to blow dry the residual solution and salt on the surface of the active metal porous material to obtain the surface modification layer of the porous active material.
[0050] Compared with Example 1, the main difference of this comparative example is that the pore size and porosity of the active metal porous material are too small.
[0051] Comparative Example 4: A method for preparing a surface modification layer of a porous active material, comprising the following steps: S1. Prepare body-centered cubic pure Zn with a pore size of 550 μm and a porosity of 60% by SLM, and perform pretreatment on it, specifically including sandblasting the outer layer of sticky powder with a sandblasting machine, and then ultrasonically treating it with a 10 vol.% perchloric acid ethanol solution for 15 minutes, then taking it out and immersing it in an ethanol solution and re-ultrasonic vibrating it for 15 minutes, the vibration frequency is set to 15 kHz, and after repeating it 3 times, use a high-purity argon gas with a purity of 99.999 vol.% to blow it dry as a whole and set it aside; S2. Mix 2 mg / mL lysozyme with 10 mmol / L 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid (HEPES) cell buffer at pH 7-8 to obtain a lysozyme type solution; use the same composition and proportion of the cell buffer to mix with 50 mL of tris(2-carboxyethyl)phosphine hydrochloride (TCEP) reducing agent, adjust the pH to 5.8 with 5 mol / L NaOH strong alkaline solvent to obtain a reducing agent solution; take the lysozyme type solution and the reducing agent solution, mix them in equal volumes, and mix them evenly by ultrasonic vibration to obtain a lysozyme mineralized biomimetic solution for standby use; S3. Use high-purity anhydrous ethanol to fully clean the inside and surface of the active metal porous material, immerse the active metal porous material obtained in S1 into the lysozyme mineralization biomimetic solution obtained in S2, and incubate in a constant temperature box at a temperature of 20°C and a humidity of 55% for 2 hours. Immerse the active metal porous material in anhydrous ethanol solvent and perform ultrasonic vibration at a frequency of 15 kHz. After completely cleaning the residual solution inside and on the surface of the porous material, use high-purity argon gas (99.999 vol.%) to blow dry the residual solution and salt on the surface of the active metal porous material to obtain the surface modification layer of the porous active material.
[0052] Compared with Example 3, the main difference of this comparative example is that no recycling treatment is performed.
[0053] Comparative Example 5: A method for preparing a surface modification layer of a porous active material, comprising the following steps: S1. Prepare a regular octahedral Zn-Mg-Cu zinc alloy with a pore size of 1310 μm and a porosity of 76% by SLM, and perform pretreatment on it, specifically including using a sandblasting machine to first sandblast the outer layer of sticky powder, and then use a 10 vol.% perchloric acid ethanol solution to ultrasonically treat it for 15 minutes, then take it out and immerse it in an ethanol solution and re-ultrasonic vibrate it for 15 minutes, the vibration frequency is set to 15 kHz, after repeating it 3 times, use a high-purity argon gas with a purity of 99.999 vol.% to blow it dry as a whole, and set it aside; S2. Mix 2 mg / mL lysozyme with 10 mmol / L N-(2-acetamido)-2-aminoethanesulfonic acid (ACES) cell buffer at pH 7-8 to obtain a lysozyme type solution; use the same composition and proportion of the cell buffer to mix with 50 mL of dithiothreitol (DTT) reducing agent, and adjust the pH to 5.8 with 5 mol / L NaOH strong alkaline solvent to obtain a reducing agent solution; take the lysozyme type solution and the reducing agent solution, mix them in equal volumes, and mix them evenly by ultrasonic vibration to obtain a lysozyme mineralized biomimetic solution for standby use; S3. Use high-purity anhydrous ethanol to fully clean the inside and surface of the active metal porous material, immerse the active metal porous material obtained in S1 into the lysozyme mineralized biomimetic solution obtained in S2, and incubate in a constant temperature box at a temperature of 20°C and a humidity of 55%. Incubate for 2 hours, take it out and put it into a circulation pump containing the lysozyme mineralized biomimetic solution obtained in S2, circulate it at 3mL / min for 20 minutes, repeat 4 times, immerse the active metal porous material in anhydrous ethanol solvent, set the vibration frequency to 15kHz for ultrasonic vibration, and after completely cleaning the residual solution inside and on the surface of the porous material, use high-purity argon (99.999vol.%) to blow dry the residual solution and salt on the surface of the active metal porous material to obtain the surface modification layer of the porous active material.
[0054] Compared with Example 4, the main difference of this comparative example is that the circulation treatment flow rate is too large.
[0055] Comparative Example 6: A method for preparing a surface modification layer of a porous active material, comprising the following steps: S1. Prepare a body-centered cubic AZ91D magnesium alloy with a pore size of 550 μm and a porosity of 60% by SLM, and perform pretreatment on it, specifically including using a sandblasting machine to first sandblast the outer layer of sticky powder, and then use a 10 vol.% perchloric acid ethanol solution to ultrasonically treat it for 15 minutes, then take it out and immerse it in an ethanol solution and re-ultrasonic vibrate it for 15 minutes, the vibration frequency is set to 15 kHz, after repeating it 3 times, use a high-purity argon gas with a purity of 99.999 vol.% to blow it dry as a whole, and set it aside; S2. Mix 2 mg / mL lysozyme with 10 mmol / L 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid (HEPES) cell buffer at pH 7-8 to obtain a lysozyme solution for later use; S3. Use high-purity anhydrous ethanol to fully clean the inside and surface of the active metal porous material, immerse the active metal porous material obtained in S1 into the lysozyme type solution obtained in S2, and incubate in a constant temperature box at a temperature of 20°C and a humidity of 55%. Incubate for 2 hours, take it out and put it into a circulation pump containing the lysozyme type solution obtained in S2, and circulate it for 18 minutes at 0.8mL / min. Repeat 3 times, immerse the active metal porous material in anhydrous ethanol solvent, set the vibration frequency to 15kHz for ultrasonic vibration, and after completely cleaning the residual solution inside and on the surface of the porous material, use high-purity argon (99.999vol.%) to blow dry the residual solution and salt on the surface of the active metal porous material to obtain the surface modification layer of the porous active material.
[0056] Compared with Example 1, the main difference of this comparative example is that no reducing agent solution is added.
[0057] The parameters of each embodiment and comparative example are shown in Table 1 below: Table 1 Setting parameters of Examples 1-4 and Comparative Examples 1-6
[0058]
[0059] The bionic modified layer on the surface of the porous active material of Example 1 was characterized and analyzed, and the results are as follows: Figure 2This is the microscopic cross-sectional morphology and element distribution diagram of the bionic modified layer on the surface of the porous active material of the present application. Through SEM and the corresponding EDS diagram, it can be seen that the interior of the treated SLM active metal porous material is covered with a hydroxyapatite protective layer with an average thickness of about 10μm (the thinnest area is 6μm, and the thickest area is close to 12μm). The thickness is relatively uniform, and the key elements in the surface bionic modified layer such as O, P, Ca, etc. are evenly distributed, which proves that the preparation method provided by the present invention successfully prepares a protective coating on the surface and inside of the SLM active metal porous material, indicating that the method proposed in the present invention is effective and can be quickly implemented.
[0060] The test results of the other embodiments are basically consistent with it.
[0061] Figure 3 This is a microscopic morphology of comparative example 1 of the present application. It can be seen from the figure that the interior of the active metal porous material in comparative example 1 is filled with a large amount of slag powder, and the surface bionic modified layer covers a small area. Since the active metal porous material in comparative example 1 has not been pre-treated, on the one hand, active metals such as Mg, Zn, etc. are very easy to react with acid or alkaline solvents, which greatly consumes the effective substances in the prepared solution, resulting in the inability to effectively modify the porous component; on the other hand, since the sticky powder in the porous component has not been removed, there is still a large amount of slag powder blocking the interior, which greatly prevents the in-situ growth of the modified layer inside the active metal porous material.
[0062] Figure 4 This is a physical picture of comparative example 2 of the present application. The active metal porous material in comparative example 2 has too large pore size and too high porosity. On the one hand, it cannot effectively support the porous structure formed by SLM, and will rapidly degrade and then collapse when slight corrosion occurs. On the other hand, the large-pore porous structure has a significantly higher affinity with body fluids after the surface treatment of the present invention, which makes it easier for liquid and active metal porous materials with high specific surface area to dissolve and fail, greatly reducing the surface protection effect of the active metal porous material.
[0063] Figure 5 This is a physical picture of comparative example 3 of the present application. The pore size of the active metal porous material in comparative example 3 is too small. Even though the wetting effect between the surface of the active metal porous material and the body fluid is significantly improved after modification, the pore size is too small to promote the effective circulation of the lysozyme mineralized biomimetic solution inside. Ultimately, the surface of the active metal porous material is first covered with a coating, which blocks the surface pores, preventing the liquid flow from further flowing into the porous structure, so that the inside is not covered with a modified layer, which greatly reduces the surface protection effect of the active metal porous material.
[0064] Figure 6This is the internal OM morphology of comparative example 4 of the present application. In comparative example 4, since the self-developed circulation pump was not used for full treatment, although the hydroxyapatite modified layer was in situ grown on the surface of the active metal porous material during the liquid immersion process, the modified layer was not fully grown inside, and the surface coating was corroded during use, which would quickly erode the internal structure of the active metal porous material, resulting in poor protection effect.
[0065] Figure 7 This is a physical picture of Example 5 of the present application. Even though the active metal porous material in Example 5 is treated with a self-developed circulation pump, the internal modification is uneven due to the excessive flow rate. That is, around the active metal porous material, due to the excessively fast flow rate of the circulation pump, the surface layer is extremely susceptible to repeated impacts of the liquid flow of the circulation pump. Even the modified layer grown in situ is very susceptible to problems such as falling off under the impact of the liquid flow. Therefore, it is difficult for the surface to be covered with a modified layer in situ. While inside the active metal porous material, due to the deceleration effect of the liquid flow of the circulation pump, there is more time for contact, reaction and further growth inside the porous structure. Therefore, it is easy for the modified layer to be covered in situ inside the active metal porous material. However, the uneven growth of the modified layer greatly limits the overall protective effect of the active metal porous material.
[0066] The performance tests of Examples 1-4 and Comparative Examples 1-6 were performed, and the specific test methods are as follows: Mechanical properties test According to GB / T 31930-2015 / ISO 13314:2011, the size of the modified and unmodified plastic is 10×10×15mm. 3 The SLM sample was placed in a universal compression device and compressed at a strain rate of 0.5 mm / min until it broke and its maximum compressive strength was read.
[0067] Corrosion performance test Select an area of 1 × 1 cm 2 The SLM samples were tested and polished after being embedded in epoxy resin. The electrochemical tests were carried out in 3.5 wt.% NaCl solution using a standard three-electrode electrochemical workstation (CS350, Wuhan, China). Pt was used as the counter electrode (CE), saturated calomel electrode (SCE) was used as the reference electrode (RE), and the specimen was used as the working electrode. The open circuit potential (OCP) measurement lasted for 3600 s to ensure that the electrode process was in a stable state during the measurement. The frequency range of the electrochemical impedance spectroscopy (EIS) measurement was set to 10 mHz - 100 kHz, and the applied perturbation amplitude was 10 mV. The polarization curves were tested in the range of OCP ± 500 mV, with a scan rate of 1 mV / s. The polarization resistance (Rp) was calculated using the electrochemical parameters (icorr, β a and β c) is determined according to the following formula:
[0068] where i corr represents the corrosion rate (mm / y), β a represents the slope of the anode branch, β c represents the slope of the cathode branch. The data were analyzed using Zview3.3 software, and all experimental measurements were repeated three times to ensure reproducibility.
[0069] Biological performance testing The effects of the samples on in vitro cytotoxicity, proliferation and differentiation were analyzed using MC3T3-E1 osteoblast precursor cells in accordance with the international standard ISO 10993-5. Before use in cytotoxicity tests, liquid extracts of the samples were prepared (37°C, 10% FBS (v / v), 3 cm 2 / ml) and sterilized by filtration, and the cytotoxicity was evaluated using the Cell Counting Kit-8 (CCK-8). BMSCs were plated at 1×10 4 The density of cells was seeded in 96-well plates (Nest, USA) for one day, and then the medium was replaced with liquid extracts of medical grade polyethylene (negative control, non-cytotoxic), α-MEM (positive control, providing reproducible cytotoxicity) containing 10% FBS (v / v) and 10% dimethyl sulfoxide (DMSO) and samples from each group (100 μL / well) for 1 day, 3 days, 5 days and 7 days. Subsequently, 10 μL of CCK-8 solution was added to each well of the plate, and the plate was incubated under light for two hours. The absorbance at 450 nm was measured. The values of the negative control wells were averaged and used as 100% cell viability. All other values were then averaged relative to their groups and compared with the negative control group.
[0070] The samples were tested for anti-Staphylococcus aureus using the following test method: LB liquid culture medium - Use a measuring cylinder to measure 100 mL of distilled water and pour it into a 250 mL reagent bottle. Use an analytical electronic balance to weigh 2.5 g of LB broth culture medium and add it to mix well. Sterilize it in a high-temperature and high-pressure steam sterilizer at 121°C for 15 min and set it aside for use.
[0071] LB solid culture medium - Use a measuring cylinder to measure 100 mL of distilled water and pour it into a 250 mL reagent bottle. Use an analytical electronic balance to weigh 2.5 g of LB broth culture medium and 1.5 g of agar powder. Add the above weighed reagents and mix them well. Sterilize them in a high-temperature and high-pressure steam sterilizer at 121°C for 15 min. When the culture medium cools to about 40-50°C, use an electric pipette to draw 15 mL of the culture medium and pour it into a disposable sterile plate.
[0072] Take two 12 mL bacterial culture tubes, add 3 mL LB liquid culture medium to each, pick a single colony from the solid culture medium of Staphylococcus aureus and add it to the liquid culture medium, and use the other tube as a blank control. Place in a constant temperature shaker (37°C, 200 rpm) and shake culture overnight (15 h).
[0073] Wipe the surface of the sample with 75% alcohol cotton, and after drying, place it in a disposable culture dish with the corresponding number, sterilize it with ultraviolet light on both sides for 30 min, and set aside.
[0074] Dilute Staphylococcus aureus to 106 CFU / mL with LB liquid medium. Add 50 μL of diluted bacterial solution to the surface of the sample, and do not add sample to the control group. Cover with a cover film and press gently. Place in a constant temperature incubator at 37℃ and culture for 18 hours.
[0075] After the culture is completed, rinse with 2 mL of sterile PBS, and dilute it 10 times with PBS solution. Take 100 μL of the dilution and evenly spread it on LB solid medium. Place it in a 37℃ constant temperature incubator for 18 hours, take it out, take pictures and record the number of colonies. Then count the colonies and calculate the antibacterial rate according to GB4789.2-2016.
[0076] Figure 8 The cell staining diagrams of Example 1 and Comparative Example 6 of the present application are shown in the figure, with Comparative Example 6 on the left and Example 1 on the right. As can be seen from the figure, after 8 weeks of growth, the cell growth on the surface of the active porous material of Comparative Example 6 is far inferior to that of the porous material treated by the present method.
[0077] Fig. 9 The figure shows the cells of the porous active material of Example 1 of the present application and the untreated one. It can be seen from the figure that after one day of growth, the cell growth on the surface of the untreated active porous material is not as good as that of the porous material treated by the present method. At the same time, due to the rapid degradation of the untreated porous material, more untreated cells die, which is not as good as the cell growth state on the surface of the porous material after the overall modification.
[0078] The specific results are shown in the following table: Table 2 Test results of Examples 1-4 and Comparative Examples 1, 3-5
[0079] Comparative Example 2 was not tested for performance because it corroded too quickly and did not form. Comparative Example 6 did not add a reducing agent and directly used a lysozyme solvent, which could not promote the growth of a hydroxyapatite film layer on the surface of the active material, so it was not tested for performance.
[0080] It can be seen from the above table that the bionic modified layer on the surface of the porous active material prepared in each embodiment of the present invention has excellent compressive strength and corrosion resistance, the antibacterial rate is about 99%, and the cell survival rate is higher than 90%, showing excellent antibacterial properties, promoting bone integration and good mechanical strength, and can achieve controllable degradation of porous alloy materials, and is suitable for bone implants.
[0081] In Comparative Example 1, since the active metal porous material has not been pre-treated, the interior is filled with a large amount of slag powder, the coverage area of the surface bionic modified layer is small, the self-corrosion current density is high, the corrosion resistance is poor, the antibacterial rate and cell survival rate are low, and the biological activity is poor; in Comparative Example 3, the pore size and porosity of the active metal porous material are too small, the surface bionic modified layer cannot grow fully, the corrosion resistance is poor, the antibacterial rate is less than 90%, and the cell survival rate is lower than 90%; in Comparative Example 4, no circulation treatment is performed, and the interior is not covered with the modified layer. After the surface coating is corroded during use, it will quickly erode the internal structure of the active metal porous material, resulting in poor protection effect and low cell survival rate; in Comparative Example 5, the circulation treatment flow rate is too large, and the growth of the modified layer is uneven, which greatly affects the overall protection effect, and the cell survival rate is only about 80%.
[0082] In summary, the hydroxyapatite biomimetic coating formed in situ on the porous active material of the present invention cleverly imitates the mineralized bone around the native bone tissue, which is very suitable for osteoblasts to adhere to its surface; and the porous active metal scaffold formed by SLM technology forms multiple micro-nano pores after surface modification, which promotes further climbing of osteoblasts and further improves their bone integration. 2+ 、Zn 2+ , Cu 1+ / Cu 2+ The plasma product exhibits excellent antibacterial properties, the preparation method is simple and fast, and it is suitable for a variety of active degradable metal materials. The formed hydroxyapatite in-situ coating is not only tightly bonded to the substrate, but also a uniform surface bionic modification layer can be obtained on the inner and outer surfaces of different types of active metal porous materials, which not only improves its strength and hardness, but also improves its corrosion resistance, thereby greatly reducing its degradation rate during actual service.
[0083] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solutions of the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a bionic modified layer on the surface of a porous active material, characterized in that The following steps are involved: S1. An active metal porous material having a pore size of 400-2000 μm and a porosity of 40-80% is prepared by SLM, and pre-treated, the pre-treatment comprising surface sandblasting, ultrasonic cleaning, repeating the ultrasonic cleaning step 3-5 times, drying, and standby; S2. The lysozyme is mixed with a cell buffer to obtain a lysozyme solution; the cell buffer is mixed with a reducing agent in the same proportion and the same composition, and the pH is adjusted to 5-6.8 to obtain a reducing agent solution; the lysozyme solution and the reducing agent solution are mixed in equal volumes to obtain a lysozyme mineralized biomimetic solution for use; S3. Immerse the active metal porous material obtained in S1 into the lysozyme mineralized biomimetic solution obtained in S2, incubate, take out and put into a circulation pump containing the lysozyme mineralized biomimetic solution obtained in S2, circulate at 0.5-2mL / min for 15-20min, repeat 3-5 times, wash and dry, and obtain the biomimetic modified layer on the surface of the porous active material.
2. A method for preparing a bionic modified layer on the surface of a porous active material according to claim 1, characterized in that: The active metal porous material described in S1 is one or more of titanium-based materials, magnesium-based materials, iron-based materials, and zinc-based materials; the porous structure in the active metal porous material described in S1 is one or more of body-centered cubic, face-centered cubic, regular octahedron, and triple minimal surface.
3. A method for preparing a bionic modified layer on the surface of a porous active material according to claim 1, characterized in that: The cleaning medium in the ultrasonic cleaning described in S1 is one or more of 5-20 vol.% perchloric acid alcohol, 3-5 vol.% nitric acid alcohol, and 10-20 vol.% dilute hydrochloric acid, the vibration frequency is 10-20 kHz, and the ultrasonic time is 10-20 min.
4. A method for preparing a biomimetic modified layer on the surface of a porous active material according to claim 1, characterized in that: S1 The drying is to dry the entire structure by high-pressure jetting of an inert gas, wherein the inert gas is 99.999 vol.% high-purity argon and / or nitrogen.
5. A method for preparing a biomimetic modified layer on the surface of a porous active material according to claim 1, characterized in that: S2 The cell buffer contains one or more of 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid, N-(2-acetamido)-2-aminoethanesulfonic acid, and 3-(N-morpholino)propanesulfonic acid; the pH of the cell buffer is 7-8.
6. A method for preparing a bionic modified layer on the surface of a porous active material according to claim 1, characterized in that: S2 The reducing agent is one or more of tris(2-carboxyethyl)phosphine hydrochloride, dithiothreitol, and tris(3-hydroxypropyl)phosphine.
7. A method for preparing a bionic modified layer on the surface of a porous active material according to claim 1, characterized in that: S2: The pH value is adjusted to 5-6.8 by using a strong alkaline solvent; the strong alkaline solvent is one or more of NaOH, KOH and Ca(OH)2.
8. A method for preparing a bionic modified layer on the surface of a porous active material according to claim 1, characterized in that: The incubation in S3 is carried out in a constant temperature box at a temperature of 18-37° C., a relative humidity of 45-60%, and an incubation time of 1.5-3 h.
9. A method for preparing a biomimetic modified layer on the surface of a porous active material according to claim 1, characterized in that: The cleaning described in S3 is to use a high-purity organic solvent to fully clean the inside and surface of the porous material; the high-purity organic solvent is one or more of anhydrous ethanol, dimethyl carbonate, and diethyl carbonate; the drying described in S3 is to use an inert gas to blow off the residual solution and salt on the surface of the active metal porous material; the inert gas is 99.999 vol.% high-purity argon and / or nitrogen.
10. A biomimetic modified layer on the surface of a porous active material, characterized in that: The porous active material surface bionic modification layer is prepared by the preparation method of any one of claims 1 to 9.
Citation Information
Patent Citations
Porous titanium-based antibacterial active material as well as preparation method and application thereof
CN115120783A
Method for preparing composite biological coating on magnesium alloy micro-arc oxidation coating
CN116618273A
Preparation method and application of intelligent self-repairing coating based on novel sealing treatment micro-arc oxidation coating
CN118563386A
Technology method for producing porous magnesium / hydroxyl apatite
CN101099873A